Multi-modality management of extraosseous Ewing sarcoma: 10-year experience from a tertiary care centre. Issue 2 (10th June 2021) - Sathyamurthy, Arvind; Singh, Ashish; Jose, Tarun; Sebastian, Patricia; Balakrishnan, Rajesh; Prabhu, Anne Jennifer; Backianathan, Selvamani
Abstract: Aim: To analyse the presentation, diagnosis and patterns of care of extraosseous Ewing sarcoma treated at our institution between 2008 and 2018. Methods: Electronic medical records of extraosseous Ewing sarcoma patients treated at our institution between January 2008 and April 2018 were reviewed. Kaplan–Meier curves were plotted to assess the overall and disease-free survival with 95% confidence intervals. A univariate analysis was carried out to assess the impact of variables such as surgical excision, completeness of surgery, completeness of chemotherapy and addition of radiation therapy on the survivorship. Results: The records of 65 patients treated at our institution were available for review. The mean age was 26·4 years. The most frequent sites of extraosseous Ewing tumour were kidney—9/65 (13·8%) and brain—10/65 (15·4%). Sixteen (24·6%) patients presented with inoperable/metastatic disease at diagnosis. The other 49 (75·4%) had localised disease at presentation. The median overall survival of the 49 non-metastatic patients was 46 months, and the disease-free survival was 45 months. Conclusion: Extraosseous Ewing sarcoma is a rare and aggressive tumour diagnosed by molecular techniques. Multi-modality treatment including surgical resection with wide margins, adjuvant radiation when indicated and completion of systemic chemotherapy results in optimum outcomes.